Zakat Empowerment Model in Islamic Boarding School - Wahyu, A. Rio Makkulau; Anwar, Wirani Aisiyah; Alamsyah; Syarifuddin; Muslimin, Supriadi; Nuringsih (Institut Agama Islam Negeri Parepare, 2023)
There are three great potentials possessed by Islamic boarding schools in their role of making the people's economy independent: This potential exists within the students, The role of Islamic boarding schools as a liaison for the surrounding community Islamic boarding schools as a resource for the surrounding community may play a role in collecting zakat and waqf. This type of research entails library research with data collection techniques beginning with the reading of references and concluding with their classification so that conclusions can be drawn regarding the concept of relevance raised regarding the model of zakat empowerment in Islamic boarding schools in Indonesia. Zakat empowerment approach at Islamic boarding schools is founded on the Quran and Hadith's teaching of doing the best for everyone, everywhere, including the local community. Islamic boarding school has implemented empowerment in education, society, culture, the environment, da'wah, health, and the economy. Consequently, via the development of the Amil zakat institution or zakat collection unit based on an Islamic boarding school, it is feasible to achieve the role and function of an Islamic boarding school, which is not just a cadre of religious thinkers/center of excellence. An institution that produces human resources for students and the local community, as well as an institution with the capacity to empower the community/agent of development.